Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 95839 by mathmax by abdo last updated on 28/May/20

solve y^((3)) −2y^((2))  +3y  −2y =sinx

solvey(3)2y(2)+3y2y=sinx

Commented by john santu last updated on 28/May/20

homogenous solution  λ^3 −2λ^2 +3λ−2=0   (λ−1)(λ^2 −λ+2)  = 0  λ = 1 , ((1± i(√7))/2)  y_h  = A_1 e^x +A_2 e^((1/2)x) (cos (((√7)/2))x+sin (((√7)/2)))

homogenoussolutionλ32λ2+3λ2=0(λ1)(λ2λ+2)=0λ=1,1±i72yh=A1ex+A2e12x(cos(72)x+sin(72))

Answered by mathmax by abdo last updated on 29/May/20

let solve it by laplace transform   (e)⇒L(y^((3))) −2L(y^((2)) )+3L(y^′ )−2L(y) =L(sinx) ⇒  x^3  L(y)−x^2 y(0)−xy^′ (0)−y^(′′) (0)−2(x^2 L(y)−xy(0)−y^′ (0))  +3(xL(y)−y(0))−2L(y) =L(sinx) ⇒  (x^3 −2x^2  +3x−2)L(y)−x^2 y(0)−xy^′ (0)−y^((2)) (0)+2xy(0)+2y^′ (0)  −3y(0) =L(sinx) ⇒  (x^3 −2x^2  +3x−2)L(y) =L(sinx)+x^2 y(0) +(2−x)y^′ (0) +(2x−3)y(0)+y^((2)) (0) ⇒  L(sinx) =∫_0 ^∞ sint e^(−xt)  dt =Im(∫_0 ^∞ e^(it−xt) dt) but  ∫_0 ^∞  e^((i−x)t) dt =[(1/(i−x))e^((i−x)t) ]_0 ^∞  =−(1/(i−x)) =(1/(x−i)) =((x+i)/(x^2  +1)) ⇒L(sinx)=(1/(x^2  +1)) ⇒  L(y) =(1/((x^2 +1)(x^3 −2x^2  +3x−2))) +((x^2 +2x−3)/(x^3 −2x^2  +3x−2))y(0)+((2−x)/(x^3 −2x^2  +3x−2))y^′ (0)+((y^((2)) (0))/(x^3 −2x^2  +3x−2))  ⇒y =L^(−1) ((1/((x^2 +1)(x^3 −2x^2  +3x−2))))+y_0 L^(−1) (((x^2  +2x−3)/(x^3 −2x^2  +3x−2))))  +y^′ (0)L^(−1) (((2−x)/(x^3 −2x^2  +3x−2))) +y^((2)) (0)L^(−1) ((1/(x^3 −2x^2  +3x−2))) wehave  x^3 −2x^2  +3x−2 =x^3 −x^2  −x^2  +3x−2 =x^2 (x−1)−(x^2 −3x+2)  =x^2 (x−1)−(x^2 −x−2x+2) =x^2 (x−1)−{x(x−1)−2(x−1)}  =x^2 (x−1)−(x−1)(x−2) =(x−1)(x^2 −x+2) ⇒  F(x) =(1/(x^3 −2x^2  +3x−2)) =(1/((x−1)(x^2 −x+2))) =(a/(x−1)) +((bx+c)/(x^2 −x+2))  ....be continued....

letsolveitbylaplacetransform(e)L(y(3))2L(y(2))+3L(y)2L(y)=L(sinx)x3L(y)x2y(0)xy(0)y(0)2(x2L(y)xy(0)y(0))+3(xL(y)y(0))2L(y)=L(sinx)(x32x2+3x2)L(y)x2y(0)xy(0)y(2)(0)+2xy(0)+2y(0)3y(0)=L(sinx)(x32x2+3x2)L(y)=L(sinx)+x2y(0)+(2x)y(0)+(2x3)y(0)+y(2)(0)L(sinx)=0sintextdt=Im(0eitxtdt)but0e(ix)tdt=[1ixe(ix)t]0=1ix=1xi=x+ix2+1L(sinx)=1x2+1L(y)=1(x2+1)(x32x2+3x2)+x2+2x3x32x2+3x2y(0)+2xx32x2+3x2y(0)+y(2)(0)x32x2+3x2y=L1(1(x2+1)(x32x2+3x2))+y0L1(x2+2x3x32x2+3x2))+y(0)L1(2xx32x2+3x2)+y(2)(0)L1(1x32x2+3x2)wehavex32x2+3x2=x3x2x2+3x2=x2(x1)(x23x+2)=x2(x1)(x2x2x+2)=x2(x1){x(x1)2(x1)}=x2(x1)(x1)(x2)=(x1)(x2x+2)F(x)=1x32x2+3x2=1(x1)(x2x+2)=ax1+bx+cx2x+2....becontinued....

Terms of Service

Privacy Policy

Contact: info@tinkutara.com